Hospital and unit variables of missed nursing care in acute care hospitals: A cross-sectional study - Jarošová, Darja; Gurková, Elena; Zeleníková, Renáta; Plevová, Ilona; Janíková, Eva (Journal of clinical nursing, 2021)
AIMS AND OBJECTIVES: To investigate hospital, unit and staff variables as the correlates of missed nursing care (MNC) in Czech hospitals. BACKGROUND: There is a considerable variability in patterns of MNC across different hospital, unit and staff characteristics. DESIGN: A cross-sectional study was conducted. The STROBE guidelines for reporting observational studies were followed for reporting of the research study. METHODS: A sample of 513 nurses working in nine acute care hospitals was recruited. MNC activities were measured with the MISSCARE Survey. Data were analysed using descriptive statistics and univariate logistic regression. RESULTS: Type of unit was confirmed as a significant predictor of MNC. Staff characteristics (nurses' work position, level of education and perceived adequacy of unit staff) and hospital variables did not contribute significantly to MNC. CONCLUSIONS: The study replicated the patterns of MNC across different conceptual approaches. MNC was influenced by work environment characteristics rather than individual staff variables. RELEVANCE TO CLINICAL PRACTICE: The results of this research showed that missed nursing care is influenced by work environment characteristics rather than individual staff variables.
Keywords: Nursing Staff, Hospital; Hospitals; pracoviště; personál sesterský nemocniční; lidé; průzkumy a dotazníky; Cross-Sectional Studies; Nursing Care; ošetřovatelská péče; nemocnice; Surveys and Questionnaires; Workplace; průřezové studie; Humans